QUALITY, EFFICACY AND SAFETY OF PHYTOMEDICINES AND PHYTOCOSMETICS - Ogendo, J. O.; Deng, A. L.; Kostyukovsky, M.; Ravid, U.; Matasyoh, J. C.; Omolo, E. O.; Kariuki, S. T.; Kamau, A. W.; Shaaya, E. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Laboratory studies were conducted to evaluate the fumigant and repellent properties of essential oils extracted from the leaves of Ocimum americanum L. against five storage insects, Sitophilus oryzae L., Rhyzopertha dominica F., Tribolium castaneum (Herbst) and Callosobruchus chinensis F. Each essential oil was tested at four (0, 1, 5 and 10 µl/L air) and five (0, 0.5, 1.0, 1.5 and 2.0 µl oil/ g grain) rates in space fumigation and choice bioassay studies, respectively, with four replicates per treatment. In space fumigation studies, leaf essential oil at 10 µl/L air 24 h after treatment, caused 88.8, 87.5, 11.3 and 100% kill of S. oryzae, R. dominica, T. castaneum and C. chinensis insects, respectively, whose corresponding LC50 values were 0.38, 0.49, NS and 0.18 µl/L air, respectively. The LC50 values varied with plant part from which the essential oil was extracted. Leaf essential oil was most efficacious (0.18-0.49 µl/L air) followed by fruit (1.15-15.07 µl/L air) and stem (3.70-34.68 µl/L air) essential oils, respectively. In the choice bioassay studies, fruit essential oil (at 2.0 µl oil/ g grain and 24 h) produced highest repellence against S. oryzae and R. dominica with PR values of 81 and 94%, respectively. Under the same conditions, the leaf essential oil had PR values of 51 and 83% against adult T. castaneum and C. chinensis insects, respectively. Results of this study demonstrate the potential use of plant volatiles as alternatives to the synthetic fumigants and their applicability for preservation of stored food commodities in subsistence agriculture.Key words: Callosobruchus chinensis, Oryzaephilus surinamensis, Rhyzopertha dominica, Sitophilus oryzae, Tribolium castaneum, Ocimum americanum, Essential oil, Fumigant toxicity, Repellence, *Corresponding author: Email: ogendojoshua@yahoo.co.uk (J.O. Ogendo)Fax: +254-51-62145/62442Cell phone: +254-722-892504; +254-738-412218